2013
DOI: 10.1016/j.febslet.2013.04.014
|View full text |Cite
|
Sign up to set email alerts
|

The type 2 anti‐Müllerian hormone receptor has splice variants that are dominant‐negative inhibitors

Abstract: Edited by Laszlo NagyKeywords: Amhr2 Dominant-negative Kinase domain Ligand binding domain Bone-morphogenetic protein responsive element a b s t r a c t Anti-Müllerian hormone (AMH) has both paracrine and hormonal actions that occur at different AMH concentrations, and in cells with different densities of its specific receptor (Amhr2). This diversity is not explained by canonical AMH signaling. We report that Amhr2 has two splice variants: Amhr2D2 (AMH binding site) and Amhr2D9/10 (kinase domain). Both spliced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 40 publications
(58 reference statements)
0
16
0
Order By: Relevance
“…The authors hypothesize that splice variants may be expressed at high levels only in a particular subset of gonadal cells and regulate AMH signaling in these cells. Alternatively, splice variants may have site specific effects independent of the presence of AMH ligand or may have a role in the transport of ligand into the cell and might be important in trafficking across the blood brain barrier (Imhoff et al, 2013). Expression of these splice variants during MD regression has not been determined and it is currently unknown what if any role they have during reproductive tract development.…”
Section: Sex Differentiation; Müllerian Duct Regression In Malesmentioning
confidence: 99%
“…The authors hypothesize that splice variants may be expressed at high levels only in a particular subset of gonadal cells and regulate AMH signaling in these cells. Alternatively, splice variants may have site specific effects independent of the presence of AMH ligand or may have a role in the transport of ligand into the cell and might be important in trafficking across the blood brain barrier (Imhoff et al, 2013). Expression of these splice variants during MD regression has not been determined and it is currently unknown what if any role they have during reproductive tract development.…”
Section: Sex Differentiation; Müllerian Duct Regression In Malesmentioning
confidence: 99%
“…Thought full-length amhr2 cDNAs from medaka [15], fugu [19] and black porgy [21] have been cloned, in vitro characterization of these receptors is not available. In mammals, the type-1 receptors that complex with AMHR2 are shared with BMPRII [54,55], allowing a well-characterized BMP luciferase assay, the BRE-luc, to be used on AMH signaling studies [36,56,57]. To test the function of sea bass Amhr2, we performed in vitro assays using the BRE-luc reporter and COS-7 cells, encouraged by the paradigm that the type-2 receptors play a more important role than type-1 receptors in the determination of specificity for the assembly of the receptor signaling complex.…”
Section: Activation Of Sea Bass Amhr2mentioning
confidence: 99%
“…Recent studies have demonstrated that the presence of signaling-competent AMHR2 complexes on the plasma membrane of mammalian cells is regulated by various mechanisms. These include the transcription of alternative spliced variants that act as dominant-negative inhibitors [57] and post-translational modifications such as cleavage of the extracellular domain, intracellular retention and/ or promiscuous disulphide-bond mediated homo-oligomerization that negatively regulate the processing of the mature receptor [70]. Similar regulation processes could be occurring on sea bass gonads.…”
Section: Expression Patterns Of Sea Bass Amh and Amhr2mentioning
confidence: 99%
“…The bioactivity of AMH was assessed, using P19 cells, as previously described (Imhoff et al, ). The P19 cells were transiently transfected with a combination of three plasmids, containing: (i) human AMHR2 ; (ii) the BMP‐responsive elements from the murine Id1 promoter fused to a luciferase reporter gene (provided by Dr. Peter ten Dijke, The Netherlands Cancer Institute, Amsterdam (Korchynskyi & ten Dijke, ; Logeart‐Avramoglou, Bourguignon, & Oudina, & Ten Dijke, Petite, ); and (iii) a Renilla reniformis luciferase (phRL‐SV40) plasmid, to control for variation in transfection efficiency (Chen, Kao, & Brown, ).…”
Section: Methodsmentioning
confidence: 99%